(untitled) (Islas, 2021)
The objective of this study is to analyze the representations of violence as social asymmetry and its social mediations, based on two female characters from the films Maria full of grace and Ixcanul. For this, the qualitative content analysis and the Atlas ti program were used. The results obtained show that the films reveal the multi-conditionality of mediations that exacerbate Latin American women’s vulnerability to violence. The verisimilitude of these images with these societies is a relevant question given the connotation that these representations have in the configuration of the social perception of reality.